pH/Redox/Lysozyme-Sensitive Hybrid Nanocarriers With Transformable Size for Multistage Drug Delivery - Liu, Zhe; Zhou, Dong; Liao, Lan (Frontiers in Bioengineering and Biotechnology, 2022)
The majority of current nanocarriers in cancer treatment fail to deliver encapsulated cargos to their final targets at therapeutic levels, which decreases ultimate efficacy. In this work, a novel core-shell nanocarrier with biodegradable property was synthesized for efficient drug release and subcellular organelle delivery. Initially, silver nanoparticles (AgNPs) were grafted with terminal double bonds originated from N, N'-bisacrylamide cystamine (BAC). Then, outer coatings consisting of chitosan (CTS) and polyvinyl alcohol (PVA) were deposited on the surface of modified AgNPs through an emulsion method. To improve stability, disulfide-containing BAC was simultaneously reintroduced to crosslink CTS. The as-prepared nanoparticles (CAB) possessed desired colloidal stability and exhibited a high drug loading efficiency of cationic anticancer agent doxorubicin (DOX). Furthermore, CAB were tailored to transform their size into ultrasmall nanovehicles responding to weak acidity, high glutathione (GSH) levels and overexpressed enzymes. The process of transformation was accompanied with sufficient DOX release from CAB. Due to the triple-sensitivity, CAB enabled DOX to accumulate in nucleus, leading to a great effect against malignant cells. In vivo assays demonstrated CAB loading DOX held excellent biosafety and superior anti-tumor capacity. Incorporating all the benefits, this proposed nanoplatform may provide valuable strategies for efficient drug delivery.